Disease Control Priorities Third Edition Is Published: A Theory of Change Is Needed for Translating Evidence to Health Policy - Ole F. Norheim (Kerman University of Medical Sciences, 2018)
How can evidence from economic evaluations of the type the Disease Control Priorities project have synthesized be translated to better priority setting? This evidence provides insights into how investing in health, particularly though priority interventions and expanded access to health insurance and prepaid care, can not only save lives but also help alleviate poverty and provide financial risk protection. The article discusses some of the relevant factors needed to develop a Theory of Change for translating economic evidence to better priority setting within countries, and proposes some key strategic choices that are necessary to achieve the desired outputs and outcomes.